Cognitive Behavioral Therapy (Cbt) In Addressing Trauma On Children And Adolescents Who Became Victims Of Violence: A Literature Review - Efri Widianti; Habsyah Saparidah Agustina (Universitas Padjadjaran, 2019)
Trauma is a circumstance in which a person experiences or witnesses death, feels threatened or seriously injured or a threat of physical integrity to oneself or others. Children and adolescents often had violence (harassment, neglect, embezzlement, or kidnapping) that can bring into trauma. The traumatic occurrence can have a serious psychological impact on children. To deal with this psychological hazard could be assisted by Cognitive Behavioral Therapy. This literature review aimed to identify the effect of CBT in supervising trauma in children and adolescents who became victims of violence to reduce the impact of trauma. Articles collected by Google Scholar, Science Direct and Pubmed Health used some keywords such as children, adolescent, CBT, trauma, and violence. The inclusion criteria consisted of quantitative research, systematic review, original research, full text, and published in English during 2007-2017. It identified 6 articles with 5 articles that were specifically related to CBT to supervise trauma. The results of the review of the five articles noted that 4 articles indicated that CBT is very effective in dealing with trauma in children and adolescent as the victims of violence, while 1 article showed that CBT is less effective in dealing with violence in children and adolescents. Thus, CBT was a potential intervention in addressing trauma in children and adolescent who became victims of violence, especially in West Java.